2017
DOI: 10.24327/ijrsr.2017.0803.0032
|View full text |Cite
|
Sign up to set email alerts
|

Increasing rate of caesarean section in lalla ded hospital, srinagar

Abstract: Increasing rate of caesarean section is matter of concern to obstetrician and society as a whole. The WHO published guidelines regarding caesarean rates in 1985 which was revised in 1994. The guideline states that the proportion of caesarean births should range between 5%-15%. This study was conducted to find out the increasing rate and indication for caesarean section and measures to decrease this rising trend. This study showed fetal distress (29.84%) as the leading cause of increasing rate of caesarean sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our scenario being similar to that in developed countries is a false satisfaction and is attributable to the alarmingly increasing rate of caesarean section in our set up and early resort to hysterectomy and inability to proceed with all the conservative measures to control the hemorrhage due to the lack of technical expertise and proper infrastructure .A study done at our hospital in 2014-2015 showed the caesarean section rate to be 60.08% in that year (Rizvi et al). 16 Massive hemorrhage was the most common intraoperative complication (11.65%), out of which…”
Section: Resultsmentioning
confidence: 99%
“…Our scenario being similar to that in developed countries is a false satisfaction and is attributable to the alarmingly increasing rate of caesarean section in our set up and early resort to hysterectomy and inability to proceed with all the conservative measures to control the hemorrhage due to the lack of technical expertise and proper infrastructure .A study done at our hospital in 2014-2015 showed the caesarean section rate to be 60.08% in that year (Rizvi et al). 16 Massive hemorrhage was the most common intraoperative complication (11.65%), out of which…”
Section: Resultsmentioning
confidence: 99%